The revised Ghent nosology for the Marfan syndrome. - Loeys, B; Dietz, H; Braverman, A; Callewaert, B; De Backer, J; Devereux, R; Hilhorst-Hofstee, Y; Jondeau, G; Faivre, L; Milewicz, D; Pyeritz, R; Sponseller, P; et al. (2010)
The diagnosis of Marfan syndrome (MFS) relies on defined clinical criteria (Ghent nosology), outlined by international expert opinion to facilitate accurate recognition of this genetic aneurysm syndrome and to improve patient management and counselling. These Ghent criteria, comprising a set of major and minor manifestations in different body systems, have proven to work well since with improving molecular techniques, confirmation of the diagnosis is possible in over 95% of patients. However, concerns with the current nosology are that some of the diagnostic criteria have not been sufficiently validated, are not applicable in children or necessitate expensive and specialised investigations. The recognition of variable clinical expression and the recently extended differential diagnosis further confound accurate diagnostic decision making. Moreover, the diagnosis of MFS--whether or not established correctly--can be stigmatising, hamper career aspirations, restrict life insurance opportunities, and cause psychosocial burden. An international expert panel has established a revised Ghent nosology, which puts more weight on the cardiovascular manifestations and in which aortic root aneurysm and ectopia lentis are the cardinal clinical features. In the absence of any family history, the presence of these two manifestations is sufficient for the unequivocal diagnosis of MFS. In absence of either of these two, the presence of a bonafide FBN1 mutation or a combination of systemic manifestations is required. For the latter a new scoring system has been designed. In this revised nosology, FBN1 testing, although not mandatory, has greater weight in the diagnostic assessment. Special considerations are given to the diagnosis of MFS in children and alternative diagnoses in adults. We anticipate that these new guidelines may delay a definitive diagnosis of MFS but will decrease the risk of premature or misdiagnosis and facilitate worldwide discussion of risk and follow-up/management guidelines.